How to increase Repurchase Intention at the Indonesian Post Office - Zain, Muhammad Fikri Bariq; Ambarwati, Rita (Universitas Proklamasi 45, 2024)
This research aims to determine the role of service quality, price, and security on customer satisfaction and their impact on repurchase intention at the Indonesian Post Office in Sidoarjo City. This research uses a quantitative approach. The population of this research consists of customers of the Indonesian Post Office in Sidoarjo City. This research involved a sample of 100 customers of the Indonesian Post Office in Sidoarjo City who were selected using accidental sampling techniques. The primary data used in this research was obtained by distributing questionnaires to respondents. Quantitative data analysis techniques using statistical methods were used to analyze the data. The statistical method used is Smart Partial Least Square (SmartPLS). Based on the research results, it was found that service quality, price, and safety influence customer satisfaction. Apart from that, it was found that service quality and price affected on repurchase intention, while security did not affect on repurchase intention. It was also found that customer satisfaction influences repurchase intention at the Indonesian Post Office in Sidoarjo City.